Skull Base Osteomyelitis Caused by Achromobacter xylosoxidans - Sunayana M. Jangla; Nalini Bhat (Journal of Krishna Institute of Medical Sciences University, 2020)
Achromobacter xylosoxidans is an aerobic, Gram negative, non-lactose fermenting rod which inhabits soil and aquatic environments. It is uncommonly encountered in human infections. When it occurs, it is associated with nosocomial infections and infection in immunocompromised individuals. Awareness of its infectious potential is important as it is multi-drug resistant and can lead to increased mortality rates. We describe a case of skull base osteomyelitis secondary to otitis media caused by Achromobacter xylosoxidans in a diabetic patient. He responded to combination treatment with carbapenem and quinolone along with blood sugar level control. Both, the clinical disorder and the causative organism are exceptional. To the best of our knowledge, no case akin to this has been reported previously in literature.